2017
DOI: 10.1136/medethics-2016-103531
|View full text |Cite
|
Sign up to set email alerts
|

Ethics consultation in paediatric and adult emergency departments: an assessment of clinical, ethical, learning and resource needs

Abstract: Nurses report a greater need for ethics education and resources compared with their physician colleagues. Ethical challenges in paediatric EDs are more prevalent than adult EDs and nurses voice specific moral distress that are different than adult EDs. These results highlight the need for a suitable educational strategy, which can be developed in collaboration with the leadership of each ED and team of hospital ethicists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
11
1
2
Order By: Relevance
“…Participants did not express paediatric speci c data. Even if the HCPs in paediatric are facing moral challenges, like complex situations with decision-making involving children´s growing autonomy and many stakeholders [24,11,6], potential differences in moral challenges between paediatrics and adult care are scarce -for instance, also in adult medicine there are plenty of situations where the adult patient is not autonomous (because they are confused, in chock, severely ill, unconscious, suffering from dementia etc) and you have a triad of patient, relatives and HCPs [46][47][48]. One could argue that it is di cult to identify moral dilemmas in pediatrics that in no circumstances can arise also in adult care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants did not express paediatric speci c data. Even if the HCPs in paediatric are facing moral challenges, like complex situations with decision-making involving children´s growing autonomy and many stakeholders [24,11,6], potential differences in moral challenges between paediatrics and adult care are scarce -for instance, also in adult medicine there are plenty of situations where the adult patient is not autonomous (because they are confused, in chock, severely ill, unconscious, suffering from dementia etc) and you have a triad of patient, relatives and HCPs [46][47][48]. One could argue that it is di cult to identify moral dilemmas in pediatrics that in no circumstances can arise also in adult care.…”
Section: Discussionmentioning
confidence: 99%
“…MCDs, and what support and what outcomes they think is important in order to help them more speci cally in handling moral challenges. Research has shown that moral challenges occurs more often in paediatric care [24]. As mentioned above, in paediatrics demanding moral challenges are involved by a triad of stakeholders including the child, family and HCPs when taking the child's best interest into account.…”
Section: Introductionmentioning
confidence: 99%
“…Caring for children who are suffering from life-threatening illnesses can lead to emotional and psychological stress, including associated moral challenges, for HCPs [8,9]. Previous research has also shown that in some settings, moral challenges occur more often in paediatric care [10].…”
Section: Introductionmentioning
confidence: 99%
“…Estudo realizado em três serviços de atendimento terciário no Canadá apontou que os enfermeiros relataram maior necessidade de educação ética, apoio adicional para lidar com sofrimento moral, gestão de conflitos com pacientes ou familiares e questões de recursos (17) .…”
Section: Introductionunclassified
“…Resultados: entre el 1 de enero y el 31 de diciembre de 2016 se contabilizaron en el último Censo de Educación Superior 936 carreras de grado en Enfermería activas, con licenciatura académica y modalidad presencial. De las 701 instituciones de enseñanza superior con planes de estudio disponibles electrónicamente, las carreras de enseñanza superior en Enfermería ofrecidos en las regiones Sudeste (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)5%) también fueron las que incluyeron a la disciplina de la bioética en el plan de estudio. Conclusión: el análisis de la enseñanza de la bioética en los planes de estudio de las carreras de Licenciatura en Enfermería de todo el país permitió concluir que estos conocimientos pueden facilitar las elecciones morales de los involucrados, contribuyendo así a la mejora de los procesos de enseñanza y de las acciones de cuidado en el ámbito de la salud.Descriptores: Educación en Enfermería.…”
unclassified